2009
DOI: 10.1103/physreva.79.052337
|View full text |Cite
|
Sign up to set email alerts
|

Thermal entanglement witness for materials with variable local spin lengths

Abstract: We show that the thermal entanglement in a spin system using only magnetic-susceptibility measurements is restricted to the insulator materials. We develop a generalization of the thermal entanglement witness that allows us to get information about the system entanglement with variable local spin lengths that can be used experimentally in conductor or insulator materials. As an application, we study thermal entanglement for the half-filled Hubbard model for linear, square, and cubic clusters. We note that it i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…It has been shown that magnetic susceptibility can be an entanglement witness [27][28][29], which is used to point out the presence of entanglement. Also momentum-momentum correlation [30,31], energies [21,22], and probability density at highly symmetric points [22] have been proposed as entanglement indicators, which reproduce the general trend of entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that magnetic susceptibility can be an entanglement witness [27][28][29], which is used to point out the presence of entanglement. Also momentum-momentum correlation [30,31], energies [21,22], and probability density at highly symmetric points [22] have been proposed as entanglement indicators, which reproduce the general trend of entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to apply the NES to the Hubbard model [54], which is a typical model for strongly correlated fermion systems and which has been widely adopted for a study on quantum information [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Despite the simplicity of the model, however, it is very difficult to obtain its exact solution except for some limited cases.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale systems belong to nonextensive systems as mentioned above. It is necessary to take into account the effect of nonextensivity, when we study the properties of quantum information of qubits, which have been mainly investigated within the BGS [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In recent years, the NES has been applied to the study on quantum information [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of criteria for the detection of entanglement based on the violation of appropriate uncertainty relations has been the focus of some interesting recent investigations [18][19][20][21][22][23]. One can establish uncertainty relations that are satisfied by all separable (pure or mixed) states and, consequently, any violation of these relations indicates that the quantum state under consideration is entangled.…”
Section: Introductionmentioning
confidence: 99%